Service Learning : An educational strategy against individualism and social exclusion - Reglero Rada, Mercedes (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
This paper claims the suitability of Service-learning as an innovative methodology that promotes social inclusion, active citizenship and enables students to contribute and build proposals as citizens within an increasin - gly individualistic and excluding society. We currently live in a context characterised by changing and sudden social risks that make the educational system to think and clearly justifies the competence-based approach as the only alternative to keep on working to build up the society and provide answers and cohesion from schools. amongst the large number of already proven achievements, Service-learning favours the social commitment of participants from a transforming perspective.
Keywords: Service learning; individuality; society of risk; inclusive education; citizenship education; competence-based approach